DEMOCRACY AND FREEDOM OF OPINION IN SOCIAL MEDIA: SENTIMENT ANALYSIS ON TWITTER - Herman Lawelai; Anwar Sadat; Ansar Suherman (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2022)
This study aims to determine public sentiment towards democracy and freedom of opinion on Twitter social media. This study analyzes and uses the data available on the Drone Emperit Academic. This study analyzes a total of 1,388,221 tweets were collected on Twitter with the tweet “Demokrasi dan Kebebasan Berpendapat”. The results of this study indicate that the public response to democracy and freedom of opinion during 2021 is positive with 54%, 43% responding negatively, and the rest responding neutrally at 3%. Thus, social media facilitates the creation of a space where people can understand, share, and interactively negotiate the meaning of protest through dialogue about democracy, although data and information disseminated through social media such as Twitter can be considered unreliable because anyone with an account can disseminate information.